Synthesis and Biological Evaluation of Anti-Parasitic Compounds - Gallagher, Ashlee (Curtin University, 2024)
Currently, there is a vital need for new treatment options for the vector-borne, parasitic protozoan diseases, which cause significant morbidity and mortality. This research focused on the synthesis of novel tetrahydroisoquinoline derivatives in order to investigate their anti-parasitic properties. 54 novel derivatives were evaluated, with 3 compounds identified as promising candidates for pre-clinical development for human African trypanosomiasis. The scaffold also showed promise for both Chagas disease and Leishmaniasis, warranting further investigation.